A novel modelling method for plate heat exchanger to predict the outlet cooling water temperature. (17th February 2019) - Guo, Yuming; Wang, Fuli; Jia, Mingxing; Niu, Dapeng
Abstract: In this paper, a modelling method for a plate heat exchanger (PHE) is proposed to predict the outlet cooling water temperature. First, the mechanistic model of PHE is developed based on the theory of heat and mass transfer. The unknown parameters in the model are identified by solving an optimization model with the sequential quadratic programming (SQP) method. Then, to improve the output precision, a data‐driven model based on the kernel partial least squares (KPLS) algorithm is developed and added to the mechanistic model in parallel to compensate the deviations between the mechanistic model outputs and the real values of outlet cooling water temperature. With the PHE running, its performance deteriorates due to the aging of the device, fouling on the plates, and other unknown factors. Therefore, a performance assessment for the model is performed, and the model updating is carried out according to the assessment results. Finally, the feasibility and efficiency of the proposed modelling method are validated by application to the PHE in a circulating cooling water system. The established model lays an important foundation for the energy‐saving optimization of the circulating cooling water system.